The Challenges and Opportunities of the Constitutional Court Decision Implementation on Recognition of the Indigenous Religions in Indonesia - Sihombing, Uli Parulian; Safa'at, Muchamamd Ali; Anshari, Tunggul; Widiarto, Eko; Salman, Radian (Universitas Airlangga, 2021)
The Constitutional Court of Indonesia has held the followers of the indigenous religion (the Penghayat) can have their own religious identity on their identity card (ID) in 2016. The 1945 Constitution of Indonesia mentions a non-discriminatory principle which has been applied by the Constitutional Court to this case. However, the implementation of the Constitutional Court decision will face challenges and opportunities on the field. The author has used of both normative and empirical methodology by providing related legal information and the result of the interview with the local leader of the indigenous religion as sources of analysing the issues. As the result of the research shows the following challenges for the implementation of the Constitutional Court decision ; a. unification of the laws, b. lack of affirmative action for the followers of the indigenous religions, c. Lack of the updated and integrated administrative data base of the citizens with the Constitutional Court decision, d. religiously and ethnically based politics effecting the decision of public officials to accommodate public services for the followers of the indigenous religions while the following opportunities of the implementation of the Constitution Court decision are the constitutional recognition and protection of the indigenous community, the existence of the National Ombudsman Commission, the rule law principle in the 1945 Constitution, final and legally binding status of the Constitutional Court decision.